Begonia nhatii, a new species (sect. Platycentrum, Begoniaceae) from Lao Cai, Northwest Vietnam - Bui, van Thanh; Nguyen, Khang Sinh; Lin, Che Wei (Phytotaxa, 2025)
Begonia nhatii, discovered from the lowland forest of Lao Cai Province in north-western Vietnam, is herein described as a species new to science. Morphologically, it is most similar to B. gulinqingensis, but can be readily distinguished by its ovate to oblong-ovate (vs. suborbicular) leaf blades that are sparsely scabrescent (vs. hirsute) on the adaxial surface, the outer tepal margins of the staminate flowers being often serrate occasionally entire (vs. always entire), shorter pistillate pedicels measuring 2–4 mm (vs. ca. 1 cm), and the presence of one or two bracteoles (vs. absent) towards the top of the pedicel.